Sustainable landscapes rating tool (SLRT). - CGIAR Research Program on Forests, Trees and Agroforestry (2018)
SLRT implemented in 4 states/provinces in Brazil, 5 in Peru, 4 in Mexico, 1 in Ecuador, 2 in Cote d’Ivoire, and 3 in Indonesia. Two-page summary profiles were created for 18 sub-national jurisdictions (provinces/states), available here: https://earthinnovation.org/state-of-jurisdictional-sustainability/